ENHANCING SCHOLARSHIP SELECTION WITH DECISION SUPPORT SYSTEMS: A SYSTEMATIC LITERATURE REVIEW OF TRANSPARENCY, EFFICIENCY, AND ACCURACY - Febriyanti, Anis; As'ad, As'ad; Abrori, Zainol; Felani, Herman; Jaya, Firman (Journal on Research and Review of Educational Innovation, 2024)
Scholarships are a form of support or appreciation given to individuals, generally for those who wish to continue their education but have economic limitations or for those who excel. A system is needed to determine worthy scholarship recipients to support decision-making. This research aims to identify the impact of a decision support system (DSS) in selecting scholarship recipients using the Systematic Literature Review (SLR) method. This research collected 15 journals from Google Scholar published from 2020 to 2024, which were analyzed based on (Quality Assessment) such as topic relevance, use of methods and criteria, and the impact of implementing a decision support system on determining scholarship recipients. The results of the analysis show that the implementation of a decision support system has a significant impact on selecting scholarship recipients who are transparent, effective, efficient, and accurate.